Food poisoning outbreak caused by diarrhoeal Bacillus Cereus: a retrospective study - Kornelius Langga Son; Andri SD Nugroho; Baning Rahayujati; La K Gozali (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: This study aimed to investigate the causative agents, source of food poisoning, and mode of food poisoning transmission in Tegalkenongo Village.Method: A retrospective cohort study was used in the epidemiological investigation for one week from 13 May 2019 – 20 May 2019. Results: Based on the investigation, Of the 303 villagers involved in the event, 188 villagers were ill with the median age of cases was 38 years old, the average incubation period was 8 hours, and the predominant symptoms were diarrhea (93.62%), nausea (84.57%), and abdominal cramps (64.89%). The contaminated chicken satay was determined as the source of contamination with an adjusted Risk Ratio (aRR) was 4.36; 95% CI 1.1538, 16.5285. Initial epidemiological features and cultures from food items served in the event and stool sample of one patient suggested that the causative agent was Bacillus Cereus which was supported by Klebsiella Pneumoniae. Conclusion: Based on the field investigation result related to symptoms and incubation period and laboratory identification, we conclude that the causative agent was diarrhoeal B. cereus.